The Reinforcement of Character Education through the Values of Local Wisdom in Folktales - Andriani, Margareta; Aulia, Fitra (Universitas Jambi, Indonesia, 2023)
Indonesia is a country that has various tribes, ethnicities, languages, religions, and customs. Each country certainly has uniqueness and local wisdom. With local wisdom, it means that a country has an identity. Indonesia consists of thirty-seven provinces that have local wisdom, such as folklores. One of them is South Sumatra Province, precisely in Pagar Alam City. Local wisdom in folklores certainly has a significant influence on character education, which seeks to instill values. This research focuses on the folklores of the three founding gods of Jagat Besemah, Pagar Alam City, South Sumatra Province. This research uses a qualitative method with interview, observation, and document techniques. The findings indicate four aspects of strengthening character education include (1) honest attitude, (2) positive thinking, (3) religion, and (4) interacting politely. Implications and future research are also discussed.